THE INFLUENCE OF THE PERSONALITY OF AQIDAH AKHLAK TEACHERS ON LEARNING MOTIVATION OF CLASS VIII STUDENTS AT MTS DEMPO DARUL MUTTAQIEN (DDM) PAGAR NATURAL CITY - Rahman; Heriyah Oktaviani; Agusti Veronika; Eri Purwanti (Al-Ibda: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The research aims to describe and analyze the relationship between the Aqidah Akhlak Teacher's Personality and the Students' Learning Motivation at MTs Dempo Darul Muttaqien (DDM) Pagar Alam. The data collection technique that the author uses in this research is to use a direct questionnaire method, observation and documentation. The population that the writer takes is 38 students at MTs Dempo Darul Muttaqien (DDM) Pagar Alam, so this research is a sample study. Based on the test, the rcount is 0,213. Then the calculated rcount is compared with the rtable price of 0,361. It is obtained that the value of rcount is smaller than rtable. Thus the hypothesis (Ha) that the researcher can’t accept, which means that there is a relationship between the personality of the Aqidah Akhlak teacher and the student's motivation to learn at MTs Dempo Darul Muttaqien (DDM) Pagar Alam. Based on the above test, it can’t be said that there is a relationship between Aqidah Teachers and Students' Learning Motivation at MTs Dempo Darul Muttaqien (DDM) Pagar Alam.